Sustainability : a philosophy of adaptive ecosystem management - Norton, Bryan G. (University of Chicago Press, 2005)
While many disciplines contribute to environmental conservation, there is little successful integration of science and social values. Arguing that the central problem in conservation is a lack of effective communication, Bryan Norton shows in Sustainability how current linguistic resources discourage any shared, multidisciplinary public deliberation over environmental goals and policy. In response, Norton develops a new, interdisciplinary approach to defining sustainability--the cornerstone of environmental policy--using philosophical and linguistic analyses to create a nonideological vocabulary.